Proceedings of IEEE INFOCOM '96. Conference on Computer Communications
DOI: 10.1109/infcom.1996.493036
|View full text |Cite
|
Sign up to set email alerts
|

Limited-range wavelength translation in all-optical networks

Abstract: This paper examines wavelength translation in all-optical wavelength-routed networks. Previous studies [4-7] have shown that wavelength translation can improve the blocking performance of these networks. However, all previous work [4-7 has assumed that Wavelength t o any output wavelength. I n contrast, alloptical wavelength translators demonstrated in the laboratory t o date [9-111 are, in general, only capable of limited translation. I n this paper we assess, for the first time, the network performance impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
1

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(108 citation statements)
references
References 12 publications
1
106
0
1
Order By: Relevance
“…The cases of no and limited wavelength conversion [18] are currently under study and will be reported elsewhere.…”
mentioning
confidence: 99%
“…The cases of no and limited wavelength conversion [18] are currently under study and will be reported elsewhere.…”
mentioning
confidence: 99%
“…Analytical models for multi-fiber networks were developed by extending the models for single-fiber wavelength-routed network [19,20]. Models for limited-range wavelength conversion can be found in [21,22,23,24,25]. The analytical models assume fixed-path routing,…”
Section: Issues and Motivationmentioning
confidence: 99%
“…The blocking probability for an optical network with limited range wavelength converters has been studied by Yates et al [67] for ring and mesh-torus topologies with fixed shortest path routing. Harai et al [59] used a hypercube network to study limited conversion with fixed shortest path routing and a first-fit wavelength selection algorithm.…”
Section: E Limited Wavelength Conversionmentioning
confidence: 99%